ANALISIS FAKTOR-FAKTOR PENGHAMBAT PEMBELAJARAN MEMBACA PERMULAAN SISWA KELAS 2 SD NEGERI 1 PERESAK - Rosa Yuliana; Muh. Taufiq; Baiq Rizki Hidayati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the factors hindering the beginning reading learningprocess for 2nd-grade students at SD Negeri 1 Peresak. Reading ability is afundamental skill in the learning process, yet many students face difficulties. Thisstudy uses a qualitative approach with a descriptive method to identify and deeplydescribe these hindering factors. Data was collected through observation,interviews, and documentation involving students, teachers, and the principal. Theresults of the study show that the hindering factors include internal aspects of thestudents, such as low learning interest, lack of motivation, and visual problems, aswell as external factors like less varied teaching methods, lack of parental support,and an unconducive learning environment. The implications of this study highlightthe importance of collaboration between the school and parents to create asupportive learning environment and to develop more innovative teaching strategiesto improve students' reading abilities.